The Mediating Role of Marketing Orientation in the Relationship between Financial Literacy and Financial Sustainability of MSEs in West Kalimantan - Kristiawati, Endang (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The development of the digital economy requires micro and small enterprises (MSEs) to adopt more adaptive marketing strategies to maintain financial sustainability. However, empirical evidence on how financial literacy influences the financial sustainability of MSEs through marketing orientation remains limited, particularly in developing regional contexts. This study aims to examine the mediating role of marketing orientation in the relationship between financial literacy and the financial sustainability of MSEs in West Kalimantan, Indonesia. This study employs a quantitative approach using survey data collected from 160 MSE owners selected through purposive sampling. Data were analyzed using linear regression, while the mediating effect was tested using the Sobel test. The results indicate that financial literacy has a significant effect on marketing orientation and financial sustainability. In addition, marketing orientation is confirmed to mediate the relationship between financial literacy and the financial sustainability of MSEs. The findings provide theoretical implications by highlighting that financial literacy and marketing orientation function as complementary capabilities in explaining MSE financial sustainability. Practically, the results suggest that strengthening financial literacy alongside market-oriented capabilities is essential for supporting the long-term sustainability of MSEs.